Analisis Dampak Pemberian Reward Terhadap Motivasi Belajar Siswa Kelas III SDN Penggaron Kidul Semarang: Menganalisis dampak dengan diberikannya reward kepada siswa untuk meningkatkan motivasi belajar - Salsa Bela, Wahyu Nuraini; Ardiyanto, Asep; Nuvitalia, Duwi (Jurnal Inovasi Pembelajaran di Sekolah, 2025)
The purpose of this study was to determine the impact of giving rewards on the learning motivation of third grade students of SDN Penggaron Kidul Semarang. In this study, the researcher used a qualitative descriptive approach using observation and interview methods. The research location was at SDN Penggaron Kidul Semarang. The results of the research on the impact of rewards on the learning motivation of third grade students show that the application of rewards has a positive impact on students. Increase students' motivation, participation, enthusiasm when the learning process takes place. It is important to understand the effective use of rewards along with the need to support the achievement of educational goals.